2017
DOI: 10.1039/c6sc05361k
|View full text |Cite|
|
Sign up to set email alerts
|

Spectroscopic observation of two-center three-electron bonded (hemi-bonded) structures of (H2S)n+ clusters in the gas phase

Abstract: The presence of a two-center three-electron (2c–3e) bonded (hemi-bonded) ion core in the (H2S)n + cluster is revealed by infrared spectroscopy combined with ab initio calculations. The stability of the hemi-bonded ion core to solvation is also proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…Above all, much of the late Dieter Asmus' seminalw ork [4][5][6][7][8][9][10][11][12][13] has apparently been forgotten, [72] but also the pioneering experimental studies of Meot-Ner, [19] Pauling [3] and Hiberty's [29] rationalization of oddelectron bond energiesi nt erms of valence-bond theory and Bock [34] and Nelsen's [35] fundamental studies on three-electron p-bonds are apparently no longerp resenti no ur general picture of bondingt heory.T his short review attempts to remind us of these classical examples of physicalo rganic chemistry, which taken on an even more importantr ole as the importance of radicals and radical ions is increasingly recognized in both biology and photovoltaics and whose importance in transition-metal chemistry has recently been reviewed. [73] Computational Section All calculations used the Gaussian 09 series of programs.…”
Section: Discussionmentioning
confidence: 99%
“…Above all, much of the late Dieter Asmus' seminalw ork [4][5][6][7][8][9][10][11][12][13] has apparently been forgotten, [72] but also the pioneering experimental studies of Meot-Ner, [19] Pauling [3] and Hiberty's [29] rationalization of oddelectron bond energiesi nt erms of valence-bond theory and Bock [34] and Nelsen's [35] fundamental studies on three-electron p-bonds are apparently no longerp resenti no ur general picture of bondingt heory.T his short review attempts to remind us of these classical examples of physicalo rganic chemistry, which taken on an even more importantr ole as the importance of radicals and radical ions is increasingly recognized in both biology and photovoltaics and whose importance in transition-metal chemistry has recently been reviewed. [73] Computational Section All calculations used the Gaussian 09 series of programs.…”
Section: Discussionmentioning
confidence: 99%
“…It is very interesting to see that that 'hemi-bond' and proton transfer type structures that have been postulated as transients in pure water cluster ionization are also present in naphthalene-water clusters, as shown in figure 14. These species should be observable spectroscopically, since recently Xie et al, using VUV photoionization in combination with IR spectroscopy, observed hemi-bonded structures in H2S clusters 106 and for (CH3SH)2 + bonded with H2O, (CH3)2CO, CH3SH and NH3. 107 Coincidence spectroscopy where mass selected photoelectron spectra can be obtained could also be applied to these PAH water clusters, as recently demonstrated for pure PAH 108 and water clusters 109 at the French synchrotron SOLEIL.…”
Section: Solvation and Reactivity In Ionized Naphthalene-water Clustersmentioning
confidence: 99%
“…Moreover, competition among multiple intermolecular interactions can be also studied by the choice of the component of the cluster. While for the S∴S hemibond and π∴π hemibond (ordinarily called “charge resonance”), detailed spectroscopic studies on their simple model cluster systems have been reported,1318 no such a study has been performed for the S∴π hemibond. Then, in the present work, the radical cation clusters of benzene (Bz) and hydrogen sulfide, [Bz-(H 2 S) n ] + , ( n = 1–4), are studied by infrared (IR) spectroscopy in the SH and CH stretch regions.…”
Section: Introductionmentioning
confidence: 99%